Phenotypic characteristics of asthma and morbidity are associated with distinct longitudinal changes in L-arginine metabolism - Alex Federman; Ryan Peterson; Ying Jin; Sunita Sharma; Fernando Holguin; Hartmut Grasemann; Meghan Dolan Althoff; Max McGrath; Juan Pablo Wisnivesky (BMJ Open Respiratory Research, 2023)
Background The L-arginine metabolome is dysregulated in asthma, though it is not understood how longitudinal changes in L-arginine metabolism differ among asthma phenotypes and relate to disease outcomes.Objectives To determine the longitudinal associations between phenotypic characteristics with L-arginine metabolites and their relationships with asthma morbidity.Methods This is a prospective cohort study of 321 patients with asthma followed semiannually for over 18 months with assessments of plasma L-arginine metabolites, asthma control, spirometry, quality of life and exacerbations. Metabolite concentrations and ratios were transformed using the natural logarithm.Results There were many differences in L-arginine metabolism among asthma phenotypes in the adjusted models. Increasing body mass index was associated with increased asymmetric dimethylarginine (ADMA) and depleted L-citrulline. Latinx was associated with increased metabolism via arginase, with higher L-ornithine, proline and L-ornithine/L-citrulline levels, and was found to have higher L-arginine availability compared with white race. With respect to asthma outcomes, increasing L-citrulline was associated with improved asthma control and increasing L-arginine and L-arginine/ADMA were associated with improved quality of life. Increased variability in L-arginine, L-arginine/ADMA, L-arginine/L-ornithine and L-arginine availability index over 12 months were associated with increased exacerbations, OR 4.70 (95% CI 1.35 to 16.37), OR 8.69 (95% CI 1.98 to 38.08), OR 4.17 (95% CI 1.40 to 12.41) and OR 4.95 (95% CI 1.42 to 17.16), respectively.Conclusions Our findings suggest that L-arginine metabolism is associated with multiple measures of asthma control and may explain, in part, the relationship between age, race/ethnicity and obesity with asthma outcomes.